2008
DOI: 10.1007/s00540-008-0609-3
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetic management of a pediatric patient with severe Williams-Campbell syndrome undergoing surgery for giant ovarian tumor

Abstract: We performed anesthetic management for a patient with severe Williams-Campbell syndrome, which is a congenital deficiency of cartilage in the subsegmental bronchial tree. An 11-year-old girl with this syndrome had labored breathing because of abdominal distension caused by a giant ovarian tumor, and removal of the tumor was scheduled. Because she had been receiving home oxygen therapy for 10 years due to hypoxia, it was possible that positive-pressure ventilation may have increased the risk of perioperative pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The limits of performance and security of the PLMA in this scenario remain undefined. Cadaver and clinical studies have confirmed that when the drainage tube is correctly positioned, the PLMA provides protection from fluid regurgitation [3,4]. Notably, PLMA design and function minimizes the likelihood of regurgitation and aspiration, and extensive evidence supports this [2].…”
Section: Discussionmentioning
confidence: 92%
“…The limits of performance and security of the PLMA in this scenario remain undefined. Cadaver and clinical studies have confirmed that when the drainage tube is correctly positioned, the PLMA provides protection from fluid regurgitation [3,4]. Notably, PLMA design and function minimizes the likelihood of regurgitation and aspiration, and extensive evidence supports this [2].…”
Section: Discussionmentioning
confidence: 92%
“…CSE is a recognized technique in such age and with compromised airway. CSE administration was reported (4,5) for children with acute tracheobronchial injury and rare syndromes, because of associated compromised airway that precluded administration of general anesthesia, as it combines the benefit of a sure onset of a heavy block and limitless anesthesia, besides free airway. Sedation is needed with pediatric regional anesthesia especially with EB to keep children in a quiet state, as struggling may result in trauma and blistering.…”
mentioning
confidence: 99%